Overview of the socio-economic consequences of heart failure - Hessel, Franz P. (Cardiovasc Diagn Ther, 2021)
Heart failure (HF) is a frequent cause of morbidity and mortality worldwide. The prevalence of HF increases, and in high-income countries, 1–2% of total healthcare expenditure is spent on HF. This article gives an overview on the impact of HF on health-related quality of life (HRQoL) and the economic burden of HF. Those suffering from HF are associated with a substantial decrease of HRQoL compared to individuals with most other chronic diseases and to individuals without HF. Therapeutic approaches, which decrease risk factors and lead to an improvement of the clinical status of patients, have a positive effect on HRQoL of the patients. Hospitalization rates have been shown to be correlated with disease severity, mortality, and HRQoL. Inpatient treatments of HF patients are cost intensive and the most important component for the economic burden of HF, responsible for at least half of direct cost. Prevention strategies, diagnostic and therapeutic approaches should focus on avoiding need for hospitalizations, and in particular, readmissions. Outpatient care including medication represents the second largest cost component. The cost of HF varies from less than 1,000 USD per patient in low-income countries to between 5,000 and 15,000 EUR in Europe, and between 17,000 and 30,000 USD in the US. There is a lack of study results on indirect costs. All study results on the socio-economic burden of HF clearly underscore the public health relevance of HF, showing a large economic burden for healthcare systems all over the world and a considerable impact on patients’ HRQoL. The results on HRQoL are relatively homogeneous, but there are large differences across countries in respect of the economic burden they have to bear. Despite the large number of studies on the socio-economic consequences of HF further research is necessary, especially on indirect cost and for low- and middle-income countries. Future studies would benefit from a greater standardization of methods and presentation of results.